The importance of the morphological study on the latin language used in the academic formation of law students of University of El Salvador - Cortez Menjivar, José Eriberto (Universidad de El Salvador, 2006)
The present is an argumentative essay in which are shown the results gotten from a research done to students of fifth year of Law Career of the University of El Salvador about the influence of Latin words used in the subject of Notarial Law. This essay is divided in five parts. The starting point of this essay is the thesis statement in which this team shows the importance of knowing morphology in Latin words; after this, it contains the theoretical framework which has the information used to develop the essay. Moreover, the body of the essay, which contains our own opinions about the results of the research; the conclusion, which explains the most important point of the research done to these students; the bibliography used to support the research and a glossary that collects the Latin words that students use in their materials